1990
DOI: 10.1016/0268-0033(90)90026-3
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar muscle size and locations from CT scans of 96 women of age 40 to 63 years

Abstract: Computed tomography scans of 96 women aged between 40 and 63 years were systematically measured to determine torso muscle moment arms and cross-sectional areas at L 2L 3, L 3L 4 and L 4L 5 disc levels. The major findings were as follows: (1) the mean muscle moment arm and area data were not different bilaterally; (2) psoas, quadratus lumborum, and latissimus dorsi muscle moment arms consistently changed at the three disc levels, while erector spinae, rectus abdominis, transverse abdominis and the oblique muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 12 publications
8
52
1
Order By: Relevance
“…This is similar to observations in other populations, such as elite cricketers 16 and other athletes, 42 who have larger multifidus CSA, erector spinae CSA, and/ or combined multifidus and erector spinae CSA on the side of the dominant arm, and contrasts observations in nondancers 7,22,33 and rowers, 36 who have symmetrical CSAs of these muscles. It is notable that, despite the aspiration in ballet of equal proficiency on either leg, there is evidence for limb preference in dance tasks and lateral bias in teaching, which is typically toward the right side.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is similar to observations in other populations, such as elite cricketers 16 and other athletes, 42 who have larger multifidus CSA, erector spinae CSA, and/ or combined multifidus and erector spinae CSA on the side of the dominant arm, and contrasts observations in nondancers 7,22,33 and rowers, 36 who have symmetrical CSAs of these muscles. It is notable that, despite the aspiration in ballet of equal proficiency on either leg, there is evidence for limb preference in dance tasks and lateral bias in teaching, which is typically toward the right side.…”
Section: Discussionsupporting
confidence: 87%
“…28 There is evidence that healthy, nonathletic individuals have no significant right-to-left-side difference in the CSA of the erector spinae, multifidus, psoas, or quadratus lumborum muscles. 7,33 Hides et al 22 reported a mean difference in multifidus CSA of less than 5% between sides across all lumbar levels. Similarly, in a group of elite oarsmen there was no asymmetry in the CSA of the multifidus, erector spinae, or psoas between sides.…”
Section: T T Resultsmentioning
confidence: 99%
“…The trajectories of the thoracic erector spinae -ICt, LTt, and ST -are modeled as straight lines [38]. Coordinates of insertions points for all global muscles (Table 1) are based on parametric anatomical studies [4,8,12,13,26,29]. The straight lines of action, shown in Fig.…”
Section: Muscle Architecturementioning
confidence: 99%
“…Models are usually formulated using from 10 to 22 different muscles about the torso. Relevant anthropometric values for these parameters can be found a variety of sources (Chaffin et al, 1990;Dumas et al, 1988;Han et al, 1992;Macintosh and Bogduk, 1986;McGill et al, 1988;Schultz et al, 1983;Tracy et al, 1989). A review of different torso anthropometries and their potential effects on optimization models can be found in McMulkin (1996).…”
Section: Estimating Internal Muscle Forcesmentioning
confidence: 99%